(3Mb GdeLfi Ydjg ai GdJfGRd Yf GdOYhi GdLfGFjI (B: s (3OQGSI JCUjdjI JWHjbjI ebGQfI (B/ s - (3LeGd TOjO Ydi GdNQHGhi s; (3TQja SjO cGeds; (3eCehf eMeO SdGegs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3GYWi GdbGfhf GdhVYi hef bHdg GdTQjYI GdESdGejI ddeLfi Ydjg Mb GdJfGRd hGdYah Yf GdLGfi ai HYV GdLQGFe GdJi JJYdb HeUGdMgGdNGUI hgPG GdMb GSJFKGQ HbjeI eYjfI Ch ecfg jefMgG GdbGfhf hjMejgG HZQV GdeMGaXI Ydi Mbhb GdeLfi Ydjg hGdeLfi Ydjg GdPi dg Mb GdJfGRd gh GdTNU GdPi GdPi SHb dg JbOje GdTchi agh UGMH GdMb GdPi jMejg GdbGfhf HfU GdJLQje s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2008s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B465-496s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJfGRd Yf GdTchis; (3GdJfGRd Yf GdWdHs; (3GdYah ai GdTQjYI GdESdGejIs; (3GdbGfhf GdEfLdjRjs; (3GdbGfhf GdShOGfjs; (3GdGJgGe GdYGes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs